2019
DOI: 10.1111/oik.05851
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the signatures of local environmental filtering and regional trait range limits in the study of trait–environment relationships

Abstract: Understanding the imprint of environmental filtering on community assembly along environmental gradients is a key objective of trait‐gradient analyses. Depending on local constraints, this filtering generally entails that species departing from an optimum trait value have lower abundances in the community. The community‐weighted mean (CWM) and variance (CWV) of trait values are then expected to depict the optimum and intensity of filtering, respectively. However, the trait distribution within the regional spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Extensive process‐based simulation of community dynamics has proved helpful to disentangle the respective influences of stochastic and trait‐based assembly processes on diversity patterns (Jabot et al , Zurell et al , Munoz et al , Denelle et al ). Indeed, community functional composition should reflect the imprint of environmental filtering (McGill et al ), while taxonomic diversity should better capture the influence of stochastic immigration–extinction dynamics (Munoz et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive process‐based simulation of community dynamics has proved helpful to disentangle the respective influences of stochastic and trait‐based assembly processes on diversity patterns (Jabot et al , Zurell et al , Munoz et al , Denelle et al ). Indeed, community functional composition should reflect the imprint of environmental filtering (McGill et al ), while taxonomic diversity should better capture the influence of stochastic immigration–extinction dynamics (Munoz et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Roel et al [22] suggested keeping an unmowed refuge zone within the grassland to increase species diversity in grasslands. Based on theoretical and empirical evidence, Doležal et al [23] argued that seasonal mowing shifts community composition, which may reduce competitive interactions and promote the coexistence of dominant and subordinate species.Plant functional traits not only determine how plants respond to environmental factors [24], but also represent important indicators of ecological strategies that affect the attributes of plant communities and ecosystems. However, knowledge of the effects of overuse on grassland plant traits and plant community stability in the context of farm management remains scarce.…”
mentioning
confidence: 99%
“…Therefore, in this study, we focus on the responses of functional traits to mowing [1,16].Varying the functional traits of plant communities along an environmental disturbance gradient is expected to reflect changes in the optimal values. Because the variation of performance around an optimal value translates into a variation in species abundances related to trait values, the mean values of the traits in communities known as the community-weighted mean (CWM) are used to reflect the local optimal trait values [24].Previous research [25] indicated that leaf traits were primarily selected in the best models for predicting biomass. The CWM of leaf area is the most important predictor [26] with an expected positive relationship [25].…”
mentioning
confidence: 99%
See 2 more Smart Citations